2009
DOI: 10.1002/app.31190
|View full text |Cite
|
Sign up to set email alerts
|

The effects of annealing (solid and melt) on the time evolution of the polymorphic structure of polyamide 6

Abstract: To understand whether and how the thermal history, especially the melting annealing, affects the polymorphism and thermal property of polyamide 6 (PA6), the temperature-modulated differential scanning calorimetry technology was used to investigate the effects of thermal histories, including annealing temperature, annealing time, and cooling rate, on the polymorphic behavior and thermal property of PA6. It was found that longer annealing time and faster cooling rate favored the formation of a crystal when PA6 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…These additional peaks can be attributed to the formation of small crystals during annealing . They were also related by some authors to an enthalpy relaxation process of the interphase between the crystalline and amorphous phases, which can be induced by isothermal crystallization or annealing process. A remarkable feature in Fig.…”
Section: Resultsmentioning
confidence: 74%
“…These additional peaks can be attributed to the formation of small crystals during annealing . They were also related by some authors to an enthalpy relaxation process of the interphase between the crystalline and amorphous phases, which can be induced by isothermal crystallization or annealing process. A remarkable feature in Fig.…”
Section: Resultsmentioning
confidence: 74%
“…In the PCLA homopolymer, the polymorphic behavior is reported to depend strongly on the thermal history. When annealed in the melt and subsequently crystallized non‐isothermally, a transition from the thermodynamically stable α‐phase to the kinetically favored γ‐phase is reported when the cooling rate increases . Another factor favoring the formation of the γ‐phase is found to be the presence of interfaces being capable of forming hydrogen bonds with the amide groups of the PCLA segments, as could be the case in the presence of PCLO polymer chains.…”
Section: Resultsmentioning
confidence: 92%
“…These studies showed the presence of three components: two crystalline phases (␣-and ␥-forms) and an amorphous fraction, where the 13 C chemical shifts of both carbons adjacent to the amide group (C1 and C5, see inset of Table 2) are particularly sensitive to the crystal form of PA6; i.e., in the ␣-form, C1 and C5 are shifted ∼3 ppm downfield from their 13 C chemical shift values in the ␥-form [28]. These differences in 13 C chemical shift between the ␣-and ␥-forms further show that the PA6 chains predominantly exist in the trans configuration (fully extended) in the ␣-form, whereas they are twisted and bended with more gauche-like character in the ␥-form.…”
Section: Conformational Changes and Local Chain Packing Analyzed By Smentioning
confidence: 99%
“…There are also other crystal forms of PA6 reported in literature, which are mainly variations of these two crystal forms, however, most of them are not stable [4,[6][7][8][9]. The molecular packing of PA6 is highly dependent on processing conditions, thermal treatment, applied stress and presence of moisture and additives [5,[10][11][12][13]. It is well known that the ␣-form can be transformed into the ␥-form by treatment with an aqueous iodine/potassium iodide solution [14,15].…”
Section: Introductionmentioning
confidence: 99%